2017
DOI: 10.1007/s41748-017-0009-7
|View full text |Cite
|
Sign up to set email alerts
|

Saudi-KAU Coupled Global Climate Model: Description and Performance

Abstract: Madden-Julian Oscillation (MJO)-like disturbances with features similar to observations, although slightly weaker. Conclusions The Saudi-KAU CGCM ability to simulate the ENSO and the MJO suggests that it is capable of making useful predictions on subseasonal to seasonal timescales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 89 publications
(57 reference statements)
4
15
0
Order By: Relevance
“…29 The model spectral truncation horizontal resolution is T42 (corresponding to 128 × 64 horizontal grid-points) with 20 vertical sigma levels. Each ensemble member differs from the others only by its different initial atmospheric conditions based on the NCEP reanalysis dataset.…”
Section: Model Description and Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…29 The model spectral truncation horizontal resolution is T42 (corresponding to 128 × 64 horizontal grid-points) with 20 vertical sigma levels. Each ensemble member differs from the others only by its different initial atmospheric conditions based on the NCEP reanalysis dataset.…”
Section: Model Description and Simulationsmentioning
confidence: 99%
“…28 Most studies are conducted using observational datasets, and the details of the mechanism connecting summertime peninsula rainfall with ENSO are not explored. The current study investigates the summer rainfall mechanism in relationship with ENSO by using a 15-member ensemble of simulations with the Saudi-King Abdulaziz University (KAU) AGCM 29 (see Methods). We also assessed the potential predictability of the model simulated rainfall in the Arabian Peninsula, which is important for local water and agriculture resources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from precipitation composite analysis are consistent with past studies (Mariotti et al 2002;Ineson and Scaife 2009;Shaman and Tziperman 2011;Niranjan Kummar et al 2016) in which it was shown that western Mediterranean, southern Europe and eastern Mediterranean regions receive more (less) than average rainfall during El Niño (La Niña) years. Moreover, in future, the climate models such as Saudi-KAU model (Almazroui et al 2017) may be used to study the impact of other climate modes and circulation patterns on the Mediterranean storm tracks.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates large uncertainty in the model-estimated precipitation, which, as mentioned earlier, was not free from limitation until now. Therefore, the use of more GCMs including newly developed Saudi-KAU model [40,41] to drive RegCM4 might be helpful to prepare a multimodel ensemble for applicationoriented tasks including rainfall harvesting in the context of climate change in the region. This paper provides a base document on the utility of climate model data.…”
Section: Resultsmentioning
confidence: 99%